Resource Technology '98 Nordic Symposium, 8-12 June 1998, Rovaniemi, Finland. Proceedings. - Salminen, Hannu; Saarikko, Jarmo; Virtanen, Eija
online version: http://urn.fi/urn.isbn:951-40-1759-5 CD-ROM cover pages